Satisfaction Index Regarding Financial Study Loans Among Students in UTHM Pagoh - Nik Aziz, Nik Azlin; Sufahani, Suliadi Firdaus (Enhanced Knowledge in Sciences and Technology, 2026)
Financial studies loans have been imperative in aiding students to pursue further studies at higher learning institutions, particularly in relation to the handling of financial components. However, the issues concerning the sufficiency, repayment and financial burden of the loan studies program have questioned the overall level of student satisfaction towards financial studies loan programs among UTHM Pagoh students. This study aims to measure the level of student satisfaction with financial study loans among students at Universiti Tun Hussein Onn Malaysia (UTHM) Pagoh and to identify the key factors influencing their satisfaction. A quantitative research design was employed using a structured questionnaire administered among 300 undergraduate students of UTHM Pagoh. The central information collected was analyzed using descriptive analysis, factor analysis and customer satisfaction index. The findings indicate that the overall level of student satisfaction towards financial studies loan programs is influenced by a complex array of factors revolving around the level of student satisfaction towards the details of loan adequacy, loan management and disbursement, loan terms and information and impact on student life and studies. The results also show that there are important relationships existing among the students’ personal characteristics and the factors that have been determined from the satisfaction components. In conclusion, the findings that have been generated from the research should be giving important insights to the students on the perceptions that they have about financial study loans, besides providing scientific evidence to the concerned parties to help improve financial aid schemes to benefit the students academically and financially.